Multifactor Authentication - A Study on User Preference, Remembering Ability, Error rate and Time Consumption - Vaithyasubramanian, S. (International Journal of Psychosocial Rehabilitation, 2020)
In information security, the key element in course of action of identifying an individual based on their username and password is Authentication. In recent years, Information technology and security environment have been changing rapidly and dramatically. Various attack methods and vulnerabilities enforce service providers to look into alternate measures to enrich security process. To enhance security of the data web developers, service providers, professionals and researchers have developed different ways for users to authenticate in order to establish their access. Authentication approaches are poised to undergo some similar transformations in response. The system to address this challenge is by utilizing and integrating various existing authentication factors. Multifactor authentication is a technique comprises of the known validation process such as alphanumeric, graphical and biometric authentication. This process is easy to use, flexible and solid in authentications to expansive scale but requires memorability of passwords and time consuming. In this paper, study on user preference, remembering ability, error rate and time consumption of Multifactor authentication process is executed.